2016
DOI: 10.1002/ccd.26720
|View full text |Cite
|
Sign up to set email alerts
|

Rapid pacing using the 0.035‐in. Retrograde left ventricular support wire in 208 cases of transcatheter aortic valve implantation and balloon aortic valvuloplasty

Abstract: Rapid ventricular pacing via the LV wire is a simple, safe and effective strategy for percutaneous aortic valve intervention and balloon aortic valvuloplasty. It eliminates the need for a temporary pacing wire with its attendant risks in the vast majority of cases. Furthermore, most pacemakers following TAVI are required late, after the first 24 hr period, by which time the TPW has already usually been removed. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 5 publications
0
27
0
1
Order By: Relevance
“…However, in 2.6% of patients, new and permanent PM implantation was required, which did not occur in our study. In another study by Hilling-Smith et al, 76 patients undergoing BAV alone and 110 patients undergoing BAV with TAVR using only LV pacing were enrolled [14]. This study provided similar findings: consistent pacing, reduced procedural time, reduced vascular complications and a possibility of early patient mobilization.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…However, in 2.6% of patients, new and permanent PM implantation was required, which did not occur in our study. In another study by Hilling-Smith et al, 76 patients undergoing BAV alone and 110 patients undergoing BAV with TAVR using only LV pacing were enrolled [14]. This study provided similar findings: consistent pacing, reduced procedural time, reduced vascular complications and a possibility of early patient mobilization.…”
Section: Discussionmentioning
confidence: 57%
“…To prevent this situation, the operator should push the guidewire towards the LV, which may increase the risk of cardiac tamponade. In our study, the final success rate of wire pacing was 100%, but in previous studies the authors reported successful pacing in 84.9%-100.0% of cases [13,14,17]. In the case of initially unsuccessful wire pacing, we scraped the distal portion of the wire where the alligator clamp should be attached with subsequently ensured pacing.…”
Section: Discussionmentioning
confidence: 65%
“…Any positioning of a dedicated pacing electrode is time-consuming and involves additional X-ray exposure. However, several published reports describe successful and safe rapid pacing using the left ventricle guidewire during valve implantation in transcatheter aortic valve replacement (TAVR) [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…2 RVP with rates of 140-200 bpm are also used routinely during transcatheter aortic valve replacements to decrease stroke volume and mean aortic pressure during balloon valvuloplasty of the aortic valve and deployment of the valve. 3 This is even used in patients with depressed ventricular function or nonrevascularized coronary disease, although the duration of RVP is minimized in these cases.…”
mentioning
confidence: 99%